Practices of solidarity as a subject of intellectual traditions in Russia and the west - V. Kovalev, Vitaliy; G. Volkov, Yuriy; V. Lubsky, Anatoly; K. Bineeva, Natalya; Z. Gubnelova, Nona (International Journal of Engineering and Technology, 2018)
This article attempts to make a comparative analysis of the assessment of solidarity practices in the intellectual tradition in Russia and the West. In the foreign intellectual tradition, four paradigms are highlighted in the study of solidarity practices: sociological, philosophical, ideological and religious. The Russian intellectual tradition includes religious and ideological paradigms. In the West, sociology and philosophies have played a major role in the study of solidarity practices, in which scientific knowledge or normative knowledge has been developed and used to put social reality under control. In the Russian intellectual tradition, practices of solidarity have been given a moral or axiological dimension.Â